Risk behaviours and prevalences of HIV and sexually transmitted infections among female sex workers in various venues in Changzhou, China. (October 2017) - Guo, Yanli; Xu, Xiaoguo; Fu, Gengfeng; Huan, Xiping; Jiang, Ning; Yin, Yueping; Chen, Xiangsheng
Female sex workers (FSWs) play an important role in the heterosexual transmission of HIV and sexually transmitted infections (STIs) in China. We conducted a cross-sectional study of 609 FSWs from various venues in Changzhou to investigate risk behaviours and prevalences of HIV and STIs among FSW subgroups. Structured questionnaires were used in face-to-face interviews to collect information. Blood and cervical specimens were collected to test for HIV, syphilis, Neisseria gonorrhoeae (NG) and Chlamydia trachomatis (CT) infections. The overall prevalences of syphilis, NG and CT were 5.6, 2.3 and 17.0%, respectively. The highest prevalence of syphilis (13.8%, P < 0.001) was observed among FSWs in low-class (LC) venues. No case of HIV infection was found. Less than half of all FSWs (40.7%) reported consistent condom use with clients during the last month. A multivariate analysis revealed a 13-fold increased risk for FSWs with NG infection to be infected with syphilis and a four-fold increased risk for FSWs aged 30–39 years to have a CT infection relative to FSWs aged 15–20 years. The prevalences of STIs were high, and risky sexual behaviours were common, especially among FSWs in LC venues. More tailored and comprehensive prevention programmes should be developed for specific FSW subgroups.